Metáforas conceptuais em reportagens com tema sobre AIDS - Mendes, Thiago Barros (2012)
Linked to “Metaphors, Discursive Genre and Argumentation” project, this study aimed to survey the linguistic expressions that update the metaphors of AIDS, making a linguistic-discursive reading of data. We used, as theoretical support, the Conceptual Metaphor Theory, designed by Lakoff and Johnson (1980; 1999); Kövecses (2002; 2005); Espíndola (2001); Sardinha (2007) and others. Our hypothesis was that the metaphors of AIDS may not be the same in 3 (three) decades of reports from VEJA and Super Interessante magazines. In our analysis, we found that disease was conceptualized in terms of military war – AIDS IS WAR – in 30 reports of 1980s, 1990s and 2000s. Another metaphor – AIDS IS PUNISHMENT – was updated only in two reports of 1980s.